2012
DOI: 10.5194/nhess-12-2463-2012
|View full text |Cite
|
Sign up to set email alerts
|

Recurring features of extreme autumnall rainfall events on the Veneto coastal area

Abstract: Abstract. Recent recurring episodes of heavy flash floodproducing rainfall events on the Veneto coastal area have renewed the interest in documenting the frequency and key dynamical ingredients of such events. A climatological analysis of the precipitation in Veneto reveals that, in comparison with the rest of the region, the coastal area is characterized by fewer rain days, lower rainfall accumulations, yet more days with heavy precipitation. If set in relation to the yearly rainfall, daily accumulation can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…Sometimes they produce a daily accumulation that can reach values as high as 40 % of the mean annual amount, even in less than 12 h, thus leading to severe flash floods, damages and human casualties (Barbi et al, 2012). Heavy precipitation over the Alps is directly (e.g., by orographic uplift) or indirectly (e.g., by orographic cyclogenesis) related to the influence of mountain ranges on atmospheric motions.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes they produce a daily accumulation that can reach values as high as 40 % of the mean annual amount, even in less than 12 h, thus leading to severe flash floods, damages and human casualties (Barbi et al, 2012). Heavy precipitation over the Alps is directly (e.g., by orographic uplift) or indirectly (e.g., by orographic cyclogenesis) related to the influence of mountain ranges on atmospheric motions.…”
Section: Introductionmentioning
confidence: 99%
“…These sites were selected because they have weather systems representative of those re- sponsible for most of the heavy precipitation and flood events affecting the Italian territory, which can be related to specific large-scale patterns . For example, the severe weather events that occurred over the Alps in recent years (Rotunno and Houze, 2007;Mariani et al, 2009;Barbi et al, 2012) or in Liguria and Lazio during the autumn of 2011 Ferretti et al, 2012;Parodi et al, 2012;Rebora et al, 2013), are directly (e.g., by orographic precipitation) or indirectly (e.g., by cyclogenesis: see Tibaldi et al, 1990) related to the influence of mountain ranges on atmospheric motions. The steep slopes of the Alps and the Apennines in the vicinity of large coastal areas of the Mediterranean, and the sea itself that acts as a large source of moisture and heat, are the key factors in determining the convergence and the rapid uplift of moist and unstable air responsible for triggering condensation and convective instability processes (Benzi et al, 1997;Rotunno and Ferretti, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The examination of four heavy rainfall events that occurred in the coastal area of northeastern Italy, a region fringed by the Alpine barrier to the north of the Adriatic Sea, revealed that synoptic rather than convective settings controlled the observed timescales of these intense rainfall events. The combined convective rainfall rates paired with the synoptic durations led to the exceptionally high rainfall accumulations observed (Barbi et al, 2012). In some particular cases, daily amounts of precipitation of 300, 400, and even 800 mm have been reported in that particular region (see, for example, Romero et al, 1997;Ramis et al, 1998).…”
Section: Synoptic Circulation Patterns That Induce Heavy Rainmentioning
confidence: 92%